The assessment of geographical borders in economic research - Małgorzata Markowska; Marek Sobolewski (Comparative Economic Research. Central and Eastern Europe, 2016)
The length of common border between two geographical units is frequently used as a basic weight in spatial analysis. The newest methodological propositions such as tests for hierarchical relations (Markowska et. al. 2014; Soko±owski et. al. 2013), regional spatial moving average and new spatial correlation coefficient (Markowska et. al. 2015) are using border lengths. In cited references new methods have been illustrated by analyses for EU NUTS2 regions. It is obvious that borders between regions belonging to different countries have different socio-economic impact than borders between regions lying in the same country. A new simple method for assesment the importance of borders is proposed in the paper. It is based on a chosen macroeconomic variable available at NUTS 2 level (e.g. GDP, infant mortality, Human Development Index). For neighboring regions bigger value is divided by smaller value giving the local importance of the given border. These measures of local border importance can be than average for borders within the same country and for borders for each pair of neighboring countries.
Keywords: 330; weighing systems; spatial analyses; spatial correlation